Does exposure to isotretinoin increase the risk for the development of inflammatory bowel disease? A meta-analysis. Issue 2 (February 2016) - Lee, Stephanie Y.; Jamal, Mohammad M.; Nguyen, Emily T.; Bechtold, Matthew L.; Nguyen, Douglas L.
Abstract : Background: Isotretinoin is a treatment option for severe nodulocystic acne. However, its use has inconsistently been associated with the development of inflammatory bowel disease (IBD). This meta-analysis aims to elucidate the association between isotretinoin exposure and the risk for IBD. Methods: A comprehensive search of PubMed/MEDLINE, CINAHL, the Cochrane database, and Google Scholar was performed (July 2015). All studies on the development of IBD in patients with or without prior exposure to isotretinoin, along with control participants, were included. Meta-analysis was carried out using the Mantel–Haenszel random effect model to assess the risk for IBD in the context of prior isotretinoin exposure. Results: In a pooled analysis of six research studies, there was no increased risk of developing IBD in patients exposed to isotretinoin compared with patients not exposed to isotretinoin [odds ratio (OR) 1.08, 95% confidence interval (CI) 0.82, 1.42, P =0.59]. Furthermore, there was no increased risk of developing Crohn's disease (OR 0.98, 95% CI 0.62, 1.55, P =0.93, I 2 =62%) or ulcerative colitis (OR 1.14, 95% CI 0.79, 1.63, P =0.49, I 2 =44%) in patients exposed to isotretinoin compared with those not exposed to the medication. Conclusion: Isotretinoin exposure is not associated with an increased risk of developing both ulcerative colitis and Crohn's disease.